Early identification of Parkinson’s disease with anxiety based on combined clinical and MRI features - Jia, Min; Yang, Shijun; Li, Shanshan; Chen, Siying; Wu, Lishuang; Li, Jinlan; Wang, Hanlin; Wang, Congping; Liu, Qunhui; Wu, Kemei (Frontiers in Aging Neuroscience, 2024)
To identify cortical and subcortical regions volume, thickness and cortical area features and the networks they constituted related to anxiety in Parkinson's disease (PD) using structural magnetic resonance imaging (sMRI), and to integrate multimodal features based on machine learning to identify PD-related anxiety anxiety in PD.A total of 219 patients with PD were retrospectively enrolled in the study. 291 sMRI features including cortical volume, subcortical volume, cortical thickness, and cortical area, as well as 17 clinical features, were extracted. Graph theory analysis was used to explore structural networks. A support vector machine (SVM) combination model, which used both sMRI and clinical features to identify participants with PD-related anxietyo-morbid PD and anxiety, was developed and evaluated. The performance of SVM models were evaluated. The mean impact value (MIV) of the feature importance evaluation algorithm was used to rank the relative importance of sMRI features and clinical features within the model.Seventeen 17 significant sMRI variables associated with co-morbid anxiety and PD PD-related anxiety were was used to build a brain structural network. And seven sMRI and 5 clinical features with statistically significant differences were incorporated into the SVM model. The comprehensive model achieved higher performance than clinical features or sMRI features did alone, with an accuracy of 0.88, a precision of 0.86, a sensitivity of 0.81, an F1-Score of 0.83, a macro-average of 0.85, a weighted-average of 0.92, an AUC of 0.88, and a result of 10-fold cross-validation of 0.91 in test set. The sMRI feature right medialorbitofrontal thickness had the highest impact on the prediction model.We identified the brain structural features and networksregions related to anxiety in PD, and developed and internally validated a comprehensive model with multimodal features in identifying